TRAINING EMPOWERMENT OF CADRES BY USING CONTROL CARDS TO PREVENT ANEMIA AMONG PREGNANT WOMEN IN DESA RANAH SINGKUANG - Erowati, Dewi; Permata Sari, Septi Indah; Marlina, Yessi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Nutrition during pregnancy plays an important role in fetal growth, the nutritional needs of pregnant women increase both in quantity and quality of nutrition. The proportion of anemia in pregnant women increased from 37.1% in 2013 to 48.9% in 2018. Anemia is linked to other health problems such as low birth weight, stunting, and child malnutrition. One of many ways to overcome the problem of anemia in pregnant women is by giving iron supplement. Pregnant women in Riau Province who received iron supplement decreased from 79% in 2018 to 65% in 2019. Therefore, it is necessary to empower cadres in preventing anemia, namely by using control cards of iron supplement consumption and education in the form of providing nutritional videos for pregnant women. The aim of this Community Service is to provide cadre training so that they will be able to educate pregnant women to increase knowledge, adherence to drinking iron supplement, and skills in processing foods high in iron. The training method used for cadres is lectures with educational media in the form of control cards, presentation handouts, showing videos on nutrition for pregnant women, and questions and answers.The training for cadres successfully improved cadre knowledge and skills, which now could educate and giving assistancy to pregnant woman consuming iron supplements and prepare high Fe foods. After receiving education from cadres, pregnant women's consumption of iron supplement increased significantly from previously not routinely every day due to forgetting or feeling nauseous after consuming iron supplement to becoming routine every day.